IMPACTION OF PERMANENT CANINES DUE TO PERSISTENCE OF PRIMARY TEETH ON DIFFERENT RADIOGRAPHIC IMAGES: CASE REPORT - Trisusanti, Ratna (Fakultas Kedokteran Gigi Unjani, 2025)
24-year-old male patient came to the Unjani Teaching Dental and Oral Hospital complaining of a disturbing residual root of the upper right front tooth and wanted to be extracted. Still, when a periapical radiograph was taken, it was found that the residual root of the tooth was a primary tooth that had not yet fallen out because there was a radiopaque picture resembling the impaction of a permanent canine tooth at the apex of the tooth. The patient never felt pain, and the complaint had never been treated before, so the patient wanted treatment to eliminate the complaint. Further supporting examination is needed, such as an occlusal radiography examination, which plays an important role in seeing the position of impaction of permanent canines in the upper and lower jaws and serves as a basis for determining the treatment plan to be carried out. This case report aims to describe the eruption disorder in the form of impaction of maxillary permanent canines due to the persistence of residual roots of primary teeth and to see in detail the position of the impaction from radiographic images of occlusal photos in the upper jaw.This case shows that the persistence of primary teeth can cause abnormalities in the direction of growth of permanent teeth into tooth impaction abnormalities found from radiographic images. DOI : 10.54052/jhds.v5n1.p51-58